Customer Evaluation On E-Service Quality Dimensions: A Study Of Internet Banking In Malaysia - Kamaludin, Mohd Ariff (2004)
The main focus of this study is to evaluate customer\'s opinions towards the service quality of Internet banking. Also, this study looks into the service quality of Internet banking by using research method to obtain data from Internet bank users in Malaysia.A set of questionnaire as designed to get the customers point of view towards the service quality of internet banking in Malaysia.